2015
DOI: 10.1111/tct.12358
|View full text |Cite
|
Sign up to set email alerts
|

Medical educators: the rich symbiosis between clinical and teaching roles

Abstract: We have found that medical practitioners bring their experience and expertise in clinical medicine to their work as educators. In addition, developing as a medical educator affects and enhances clinical practice. These findings have important implications for those charged with the development of medical education and medical educators themselves, as well as the patients that they care for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
9
1
Order By: Relevance
“…CEs described educating as being inherent in their therapist role which involved educating patients and their family members on a daily basis. This finding contrasts with existing literature on medical educators’ experiences in which medical educators perceived the similarities between clinical and educator roles predominantly as the transferability of communication skills and diagnostic thinking from clinical practice to educational situations 18. This is likely due to the difference in job nature between doctors and therapists - that is, patient education occupies a larger proportion of time in therapy work compared with medical work.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…CEs described educating as being inherent in their therapist role which involved educating patients and their family members on a daily basis. This finding contrasts with existing literature on medical educators’ experiences in which medical educators perceived the similarities between clinical and educator roles predominantly as the transferability of communication skills and diagnostic thinking from clinical practice to educational situations 18. This is likely due to the difference in job nature between doctors and therapists - that is, patient education occupies a larger proportion of time in therapy work compared with medical work.…”
Section: Discussioncontrasting
confidence: 82%
“…These unpredictable interruptions caused by turning the identity ‘on’ and ‘off’ may cause heightened distress 13. Lake and Bell’s study18 showed that medical educators constructed common meanings between their educator and clinician roles and described a reciprocal relationship between both roles. However, it was unclear if the shared meanings between educator and clinician roles would facilitate identity verification.…”
Section: Introductionmentioning
confidence: 99%
“…Participants typically viewed their multiple identities in a hierarchical fashion, with activities related to their clinical identity taking precedence. 22 Many viewed being a GP and a supervisor as complementary, 23,24 with supervisors establishing a sense of balance between their roles over time. 22 As GPs incorporated supervision into their daily clinical work, the two roles became more synchronous.…”
Section: Discussionmentioning
confidence: 99%
“…It is the teachers in the two latter groups who experience less tensions and who are more likely to see positive connections between the different roles. For example, these teachers hold that expertise in clinical practice reinforces their credibility as a teacher (Davies et al 2011) or that having a formal educational role enhances their status amongst clinical peers (Lake and Bell 2016). Other positive connections between the different roles concern strongly holding the view that being a physician implicitly also means being a teacher, or seeing the development in one role as positively impacting on the other (Steinert and Macdonald 2015;Van Lankveld et al 2017a).…”
Section: Developing a Teacher Identity In Health Professions Educationmentioning
confidence: 99%